Photochemical Reaction of 9-Bromo-Fluorene - Garg, S.; Kohli, J.C. (Asian Journal of Chemistry, 2010)
With a view to examining the photochemical behaviour of some typical aromatic halogenated compounds, irradiation of 9-bromo-fluorene was done in benzene and toluene which led to produce two fluorenone derivatives in each case.